Dynamiques spatiales récentes du Parc National du Banco (PNB) et stratégies de gestion communautaire durable de ses ressources forestières (District d’Abidjan en Côte d’Ivoire) - Nakouma Sako; Gérard Beltrando (EchoGéo)
The recent space-time dynamics of the forest of the National Banco Parc, located inside the administrative limits of the district of Abidjan in Ivory Coast, caracterised by the post-classifying comparison of the classes of two multispectral images Spot 1 and 2 catches in January 1992 and 2002 (scene of 60 X 60 km² centered on the town of Abidjan, analyzes of three multispectral channels, XS1, XS2, XS3, pixel 20 m). Floristic inventories, carried out during the summer 2008 out of 196 points, according to a North-South and East-West transects, as well as socio-demographic investigations (250 people chosen by chance in 6 bordering villages) and of the observations of ground made it possible to check and correct the cartographic results and to determine the points of view of the local actors on the future of the PNB. The results of the inventories show a great vegetable diversity. The surface analyses of the types of vegetation charted starting from the image of under scene Spot (2002) centered on the park show a prevalence of the forest formations with approximately 4 000 ha either 68% of the surface in 2002 against 1.746 ha or 31% in 1992. The major exploitations of the vegetation are located on the margins of the park. On the other hand, inside the forest plantations of the 1940’s and the “natural” forests know positive evolutions. The results of the investigations into the perception of the populations also state that 67% of the questioned people estimate that the improvement of the current policy of management of the PNB and its installation constitutes adequate means for its conservation and its durable development.